(untitled) (Universal International Scientific Journal, 2026)
Observation of the work of a number of music teachers shows that in order to improve their professional skills, the following is necessary: ​​to educate the teacher’s civic responsibility and public duty; to implement a developing educational process aimed at forming professional enthusiasm, interest in all aspects of musical and pedagogical activity; to deepen psychological and pedagogical knowledge that will help the teacher master the culture of communication with students and the means of pedagogical influence on them (individual and collective); to continuously improve and educate further pedagogical training, professional level.